Interaction between endotoxin and human monocytes: characteristics of the binding of 3H-labeled lipopolysaccharide and 51Cr-labeled lipid A before and after the induction of endotoxin tolerance. - Larsen, N E (1984)
Salmonella typhi endotoxin (lipopolysaccharide, LPS) was labeled with tritium and purified by gel filtration. Using this preparation, we found that binding of 3H-labeled LPS (3H-LPS) to isolated human monocytes consisted of a rapid (t1/2 less than 5 min), reversible, temperature-independent phase of surface adsorption that was followed by a slower (t1/2 greater than 20 min) period of binding that was irreversible and temperature-dependent. The interactions between 3H-LPS and monocytes that we measured were dependent both on the concentration of LPS and the cell number. We observed an apparent decrease in 3H-LPS surface binding after initial treatment of the cells with LPS, which was most likely due to an acquired reduction in the number of sites on the monocyte membrane available for the binding of LPS. Estimates of the parameters of the binding of 3H-LPS were calculated from a double-reciprocal plot (1/bound vs. 1/free) of the surface binding data and suggest that the relative binding affinity (Kd) for 3H-LPS was unchanged after pretreatment of the monocytes with LPS; however, the total number of LPS binding sites appeared to be reduced by this manipulation. The results of competition binding experiments also suggest that the binding affinity for 3H-LPS was the same before and after incubation of the cells with LPS. Lipid A, which we extracted from LPS and labeled with chromium-51, exhibited a binding affinity similar to that of 3H-LPS and, like 3H-LPS, could be displaced from the cells by competing concentrations of unfractionated LPS; however, the kinetics of binding of the two labeled ligands differed considerably. Our results suggest that exposure of monocytes to LPS may alter the ability of these cells to interact with, and consequently respond to, LPS.